Paradigmatische und syntagmatische bedeutungen des praterits im modernen deutsch - Krivenko, V.P. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2009)
The present article covers the rather debatable issue of temporal, actional and extemporal interpretation of the German preterit and its functioning in different contexts. The views of different researchers of the German language on the problem are described and compared and a conclusion about the temporal semantics of the German grammar temporal forms is made. The article studies the two main functions of the preterit, the imperfective (describing) function and the aoristic (narrative) function, and it also describes its other (secondary) meanings in which it can be used depending on the surrounding context. Стаття присвячена ще досить дискусійному питанню щодо темпорального, акціонального та атемпорального тлумачення німецького претеріта та його функціонуваннюу різних контекстах. В статті описуються та порівнюються точки зору різних германістів на цю проблему: робиться висновок щодо темпоральної семантики німецьких граматичних часових форм. Аналізуються дві основні функції претеріта: імперфективна (описова) та аористична (розповідна), а такожописуютьсяйого інші (другорядні) значення, в яких він можевживатисьв залежності від оточуючогоконтексту. Статья посвящена еще достаточно дискуссионному вопросу о темпоральном, акциональном и атемпоральном толкованиинемецкогопретерита и его функционированияв разных контекстах. В статье описываютсяи сравниваются точки зрения разных германистов на эту проблему, делается вывод относительно темпоральной семантики немецких грамматических временных форм. Анализируются две основные функции претерита: имперфективная (описательная) и аористическая (повествовательная), а также описываютсяего остальные (второстепенные) значения, в которых он может употребляться в зависимости от окружающего контекста.
Keywords: акціональність; аористична функція; атемпоральність; темпоральність; імперфективна функція; парадигматичне значення; синтагматичне значення; actionality; aoristic function; extemporality; imperfective function; paradigmatic meaning; syntagmatic meaning; temporality